Creativity and other Learner Characteristics in Acquiring Language - Gulrukh Yusupova (Researchparks Publishing, 2022)
The study describes one of the more complicated steps in a language learner's phycology while learning a second language. As second language acquisition is influenced by a variety of elements and traits (Zafar & Meenakshi, 2012), this research will focus on the practical consequences of the broad physiological concept of creativity. The research's relevance is in identifying the gap between scientific knowledge and practical application in learning a second language from a physiological standpoint. The study's goal is to put the construct of learners' phycology-creativity to the test in order to see how it can aid in the acquisition of a second language. The research takes into account prior efforts in this subject such as Sternberg (2006), Chamurro-Premusic (2011), Simonton (2008), and others.